Gray's anatomy for students - Drake, Richard L., 4 Ph.D.0 16; 1825-1861. Vogl, Wayne.;Mitchell, Adam W. M.;Tibbitts, Richard.;Richardson, Paul.;Horn, Ansell.;Gray, Henry; 5 (Philadelphia, PA : Churchill Livingstone/Elsevier, 2010)
Text and over one thousand illustrations describe and explain features of the human anatomy, covering the back, thorax, abdomen, pelvis and perineum, lower and upper limbs, and head and neck, and includes clinical cases and questions.
The body -- Back -- Thorax -- Abdomen -- Pelvis and perineum -- Lower limb -- Upper limb -- Head and neck.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Human anatomy.;Anatomy.;Human anatomy; 20; 2